Peningkatan Pengetahuan Masyarakat Tentang Penanganan Orang Dengan Gangguan Jiwa di Desa Cijagang, Kecamatan Cikalong Kulon, Cianjur, Jawa Barat: Peningkatan Pengetahuan Masyarakat Tentang Penanganan Orang Dengan Gangguan Jiwa di Desa Cijagang, Kecamatan Cikalong Kulon, Cianjur, Jawa Barat - Mekarsari, Tria Cahyani; Esterilita, Mari; Kartikawati, Dewi (J.Abdimas: Community Health, 2024)
This This community service aims to describe the practices of community social workers in dealing with the lack of understanding of the Cijagang village community towards people with mental disorders. This community service was carried out in the Cijagang village area, Cikalong Kulon subdistrict, Cianjur, West Java. The method used in this community service is a macro social work approach with three stages, namely, the initial stage, which includes social initiation, at this stage the author carries out home visits, transect walks, and community involvement, social organizing is carried out. together with village officials such as RT, RW, hamlet heads, and PKK members, social assessments, which at this stage are carried out using macro social work technology, namely Methodology Participatory Assessment (MPA), and social planning are planned using focus group discussion techniques (FGD). Then the second stage is implementing the intervention in the form of providing outreach to residents, and the final stage which includes evaluation and termination by holding a workshop to explain the activities carried out and say goodbye. The results of this community service can be seen through the average pretest posttest score. In the pretest results, the average knowledge of the community regarding handling people with mental disorders was 67.36 and the average posttest showed an increase in knowledge to 76.84. The conclusion of community service is that there has been an increase in knowledge in the community regarding the treatment of people with mental disorders after providing socialization regarding the treatment of people with mental disorders.